Interaction with adipocyte stromal cells induces breast cancer malignancy via S100A7 upregulation in breast cancer microenvironment - Sakurai, Minako (Breast Cancer Res, 2017)
BACKGROUND: Breast adipocytes play important roles in both the development and function of mammary epithelial cells. Therefore, carcinoma–adipose stromal cell (ASC) interactions have been considered pivotal in supporting tumor growth in breast cancer. In addition, it has been demonstrated that the biological features of cancer-associated adipocytes differ from those of normal ASCs. Therefore, we investigated an interaction between ASCs and carcinoma cell lines to identify genes associated with ASC invasion of carcinoma cells. METHODS: 3T3-L1 ASC-derived conditioned medium (CM) was treated to measure the proliferation rate of breast cancer cells. To further examine the effect of ASCs, breast cancer cells were cocultivated with either primary human or 3T3-L1 ASCs for migration assays, DNA microarrays, quantitative real-time polymerase chain reactions, and Western blotting experiments. Furthermore, immunoreactivity of S100A7, the most upregulated gene in MCF7, after coculture with ASCs was evaluated for 150 breast cancer tissues to statistically analyze its association with clinicopathological parameters. RESULTS: We first confirmed that ASC-derived CM treatment enhanced the cell proliferation rate of MCF7, T47D, SK-BR-3, and ZR-75-1 cell lines, whereas the migration rate of breast cancer cells was promoted by coculture with ASCs. We identified that a small calcium-binding protein, S100A7, was markedly upregulated (by 5.8-fold) in MCF7 cells after coculture with primary human ASCs. Knockdown of S100A7 significantly suppressed ASC-stimulated cell proliferation and migration rate, indicating a possible involvement of S100A7 in the carcinoma–ASC interaction in breast tumors. Furthermore, strong S100A7 immunoreactivity was detected at the invasive front of adipose stromal tissues compared with that at the intratumoral area. The status of S100A7 was also significantly correlated with adverse pathological parameters, and multivariate analysis revealed that S100A7 could be an independent prognostic marker for a poor relapse-free survival rate. Moreover, induction of oncostatin M was detected in cancer-stimulated ASCs, whereas the downstream S100A7 binding proteins/receptor for advanced glycation endproducts were significantly upregulated in correspondence with S100A7 expression in breast cancer cells after coculture with ASCs. CONCLUSIONS: The results of our study suggest that paracrine production of cytokines from ASCs stimulates breast carcinoma cell growth via upregulation of S100A7 expression in breast cancer cell lines. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13058-017-0863-0) contains supplementary material, which is available to authorized users.